The integration of pedagogical ideas of A. S. Makarenko in the activities of modern comprehensive and higher education institutions (Pedagogy of Higher and Secondary Education, 2015)
Volikova M. N. The integration of pedagogical ideas of A. S. Makarenko in the activities of modern comprehensive and higher education institutions.The article analyzes the pedagogical ideas and views of outstanding Ukrainian educator A. S. Makarenko in the context of contemporary educational realities: comprehensive development and self-esteem, the formation of personal maturity, peculiarities of professional activity of a teacher in the context of a humanistic education. It was clarified how the thoughts of A.S. Makarenko about teaching technique and skill are current today. The idea that the actual path of the educational system development of the twenty-first century should be the dialectical development of pedagogical theory and practice of the twentieth century has been substantiated.
Keywords: integration; pedagogical heritage of A. S. Makarenko; education; upbringing